2002
DOI: 10.1002/cm.10010
|View full text |Cite
|
Sign up to set email alerts
|

Expression of constructs of the neuronal isoform of myosin‐Va interferes with the distribution of melanosomes and other vesicles in melanoma cells

Abstract: Myosin-Va has been implicated in melanosome translocation, but the exact molecular mechanisms underlying this function are not known. In the dilute, S91 melanoma cells, melanosomes move to the cell periphery but do not accumulate in the tips of dendrites as occurs in wild-type B16 melanocytes; rather, they return and accumulate primarily at the pericentrosomal region in a microtubule-dependent manner. Expression of the full-length neuronal isoform of myosin-Va in S91 cells causes melanosomes to disperse, occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The physiological significance of the latter interaction is evident on the basis of the following observations: (1) deletion of exon F by mutations in the alternative splicing sites causes the dilute phenotype (i.e. perinuclear aggregation of melanosomes) (Seperack et al, 1995;Huang et al, 1998); (2) expression of brain myosin-Va lacking an exon F cannot rescue the phenotype of dilute-derived melanocytes (Wu et al, 2002b), and expression of MC myosin-Va-tail, but not of brain myosin-Va-tail, induces perinuclear aggregation of melanosomes (Wu et al, 2002b;da Silva Bizario et al, 2002;Westbroek et al, 2003); and (3) Slac2-a mutants lacking the exon-F-binding site cannot support normal melanosome distribution in melan-a cells (Kuroda et al, 2003). We therefore concluded that both interaction sites in Slac2-a identified in this study, the myosin-Va-GT-binding site and the myosin-Vaexon-F-binding site, are essential for melanosome transport in melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological significance of the latter interaction is evident on the basis of the following observations: (1) deletion of exon F by mutations in the alternative splicing sites causes the dilute phenotype (i.e. perinuclear aggregation of melanosomes) (Seperack et al, 1995;Huang et al, 1998); (2) expression of brain myosin-Va lacking an exon F cannot rescue the phenotype of dilute-derived melanocytes (Wu et al, 2002b), and expression of MC myosin-Va-tail, but not of brain myosin-Va-tail, induces perinuclear aggregation of melanosomes (Wu et al, 2002b;da Silva Bizario et al, 2002;Westbroek et al, 2003); and (3) Slac2-a mutants lacking the exon-F-binding site cannot support normal melanosome distribution in melan-a cells (Kuroda et al, 2003). We therefore concluded that both interaction sites in Slac2-a identified in this study, the myosin-Va-GT-binding site and the myosin-Vaexon-F-binding site, are essential for melanosome transport in melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…that the delay in the Golgi disassembly induced by BFA is much more severe in BDM-than in ML7-treated cells, suggest the participation of a second (processive) motor that subsequently helps move the newly generated transport carriers to their final destination (in this case the ER). In this respect, myosins V and VI are processive motors (which means that it takes successive steps along the actin filament) that are reported to be located in the Golgi complex and involved in vesicular trafficking in some cell types (Nascimento et al, 1997;Buss et al, 1998;DePina and Langford, 1999;Miller and Sheetz, 2000;Schott et al, 2002;da Silva Bizario et al, 2002) and, thus, they could be acting in tandem with myosin II at the Golgi complex. However, we cannot completely rule out the sole implication of myosin II, because despite that this motor does not take successive steps along the actin filament, multiple myosin II moieties could show successive steps along a filament (a processive movement).…”
Section: Actin-based Motors and Nonmuscle Myosin II In Golgi-to-er Pamentioning
confidence: 99%
“…For example, vertebrate myosin Va moves melanosomes in melanocytes ( Provance et al, 1996 ; Nascimento et al, 1997 ; Wu et al, 1997 ; Rogers and Gelfand, 1998 ), the smooth ER in brain Purkinje cells ( Takagishi et al, 1996 ), membranous vesicles in nerve cells ( Evans et al, 1998 ), and chromaffin vesicles ( Rose et al, 2003 ). Moreover, within a single cell type, myosin Va likely moves more than one type of cargo ( da Silva Bizario et al, 2002 ). In S. cerevisiae , the myosin V, Myo2p, is essential and transports secretory vesicles, the vacuole, late Golgi, and peroxisomes ( Govindan et al, 1995 ; Hill et al, 1996 ; Catlett and Weisman, 1998 ; Schott et al, 1999 ; Karpova et al, 2000 ; Hoepfner et al, 2001 ; Rossanese et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%